Analisa Persaingan Bisnis Antara Merek Mie Sedap Dan Mie Indomie - Anneira Azzahra; Mia Mulyani Zahra; Syamsul Hidayat (Universitas Sains dan Teknologi Komputer, 2024)
People's lives have begun to change in this era of globalization, everything that is needed is required to be fast and practical. Several needs, including food, have become instantaneous, creating a very high level of development in the food business, especially in Indonesia. . With the current busy activities of society, business actors have the opportunity to create fast food products (Hernawan, 2019). Therefore, new businesses began to emerge known as fast food or fast food. Instant noodles are popular with everyone, both young and old. Therefore, the focus of the research entitled